FEM modelling and analysis of reinforced concrete section with lightweight blocks infill - Wahyuni, Ade; Vimonsatit, Vanissorn; Nikraz, Hamid (CRC Press/Balkema, 2012)
In an attempt to reduce the self weight of reinforced concrete structures, a new development of lightweight sandwich reinforced concrete (LSRC) section has been proposed as an alternative option to solid section. LSRC section is a reinforced concrete section which contains lightweight blocks as infill material. An experimental investigation into the strength of LSRC beams has shown promising results under flexural tests. To ensure the serviceability of LSRC members under service load, it is necessary to accurately predict the cracking and deflection of this section. This paper will focus on analysing the behaviour of the tested beam specimens after cracking occurs. ANSYS 12.1 was employed to study the crack propagation of LSRC beams under bending. The numerical model shows the crack in the area of AAC blocks which associates with the brittle failure of LSRC beams. The crack propagation of the beams analysed by ANSYS agrees well with the results from the experimental investigation.